The Urgency of Applying the Principles of Simple, Fast and Low Cost Justice in the Execution of Industrial Relations Court Decisions in Indonesia - Farida, Ema; Suriaatmadja, Toto Tohir; Sundary, Rini Irianti (Yayasan Sinergi Kawula Muda, 2024)
This Research Aims To Analyze The Urgency Of Applying The Principles Of Simple, Fast And Low Cost Trials In The Execution Of Industrial Relations Court Decisions In Indonesia. The Research Specification Used By The Author In This Research Is Descriptive Analytical Research, Namely a Research Method That Aims To Get An Overview Of The Symptoms Being Studied At The Present Time And Then Relate Them To Legal Norms Or Statutory Regulations The data analysis used in this research is Qualitative Data Analysis. Analyzing the content of legal documents, court decisions, and related literature to identify themes, patterns, and trends relevant to the research questions. Research results prove that The application of the principles of simple, fast and low-cost justice in the execution of Industrial Relations Court (PHI) decisions in Indonesia has a very important urgency. Here are some reasons why this is so necessary: Protection of Labor Rights: Most of the cases submitted to PHI involve labor rights and worker welfare. Delays in executing decisions may result in workers not being able to immediately obtain their rights, such as delayed wages, leave rights, or other rights.